Lessons from the Winter Paralympic Games disclosing the epidemiology of winter sports injury in paralytic athletes: a meta-analysis - Wu, F.; Liu, Y.; Zhuang, M. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background In this study, the incidence rate of the injury in Winter Paralympic Games was summarized. Besides, to testify the underlying factors of injury incidence heterogeneity, the difference of these events incidence between different Paralympic Winter Games was investigated by meta regression analysis.